Usefulness of Sarilumab in Patients with Rheumatoid Arthritis after Regression of Lymphoproliferative Disorders - Yoshifumi Tada; Akira Maeyama; Tomonobu Hagio; Mariko Sakai; Akihito Maruyama; Takuaki Yamamoto (Case Reports in Rheumatology)
Lymphoproliferative disorders (LPDs) are serious complications associated with rheumatoid arthritis (RA) treatment that mostly occur during methotrexate (MTX) treatment. Cessation of MTX may induce regression of LPDs but is often followed by a flare of RA. Here, we describe two patients with RA flares after the discontinuation of MTX due to LPDs and sarilumab was useful for the treatment of RA without a relapse of LPDs. Patient 1 was an 84-year-old woman, who developed an LPD in the pharyngeal region after 7 years of MTX treatment. Discontinuation of MTX induced regression of LPD but RA flared within 6 months. Administration of sarilumab, in addition to salazosulfapyridine and prednisolone, reduced the RA activity without LPD relapse. Patient 2 was a 76-year-old man, who developed LPD in the pharyngeal region after 5 years of MTX treatment. Discontinuation of MTX induced regression of LPD, but soon RA flared. Although treatment with tocilizumab (TCZ) was effective in controlling RA, it flared again after 2 years. TCZ was switched to sarilumab and RA was in remission. LPD did not recur during these periods.